Solenoids in holomorphic dynamics - Zeidan, Ismael A. (My University, 2026)
This Master's thesis is a report on the work of Hubbard and Oberste-Vorth. We study the emergence of solenoidal structures in the dynamics of complex Hénon maps, with particular emphasis on their realization through inductive limit constructions... See PDF for full text.
Keywords: Mathematics